Methodological Approaches to Managerial Diagnostics and Expert Analytics in Corporate Governance - Zaika Svitlana; Заїка С.; Zaika Sz. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. In today's environment, businesses are forced to respond quickly to numerous external and internal factors that affect their operations. Management diagnostics and expert analytics play an important role in the management process, providing managers with the necessary information to make informed decisions and assess the prospects of the enterprise. However, the absence of a clear methodological basis and differentiation of these approaches complicates their effective use in enterprise management. The article examines the conceptual foundations and methodological approaches to management diagnostics and expert analytics as tools for effective enterprise management. Management diagnostics is defined as a systematic process of research and evaluation of enterprise functioning aimed at analyzing economic, financial and organizational indicators, which is based on the study of actual performance results, internal and external factors of influence, as well as other relevant information with a view to identifying problems, determining reserves for improvement, assessing the effectiveness of management decisions and formulating recommendations for the future development of an enterprise. Instead, expert analytics is focused on long-term forecasting, analyzing the relationships between internal and external factors, and forming the basis for strategic decisions. The article highlights the main differences between these approaches in terms of such characteristics as purpose, objectives, methods, subject and object of research, as well as the results of their application Management diagnostics is aimed at analyzing current processes and effectively solving operational problems, while expert analytics forms the information basis for long-term decision-making, taking into account macroeconomic and industry changes. Particular attention is paid to the complementarity of these approaches in modern management, which allows creating a holistic analysis system aimed at maintaining the efficiency of the enterprise in the short and long term. It is established that the integration of management diagnostics and expert analytics allows managers to get a clear picture of the state of the enterprise, potential threats and opportunities for development.

A mai környezetben a vállalkozások kénytelenek gyorsan reagálni a működésüket befolyásoló számos külső és belső tényezőre. A menedzsmentdiagnosztika és a szakértői analitika fontos szerepet játszik a menedzsmentfolyamatban, mivel a vezetők rendelkezésére bocsátja a megalapozott döntések meghozatalához és a vállalkozás kilátásainak értékeléséhez szükséges információkat. Azonban e megközelítések világos módszertani alapjának és megkülönböztetésének hiánya megnehezíti hatékony alkalmazásukat a vállalatirányításban. A cikk a menedzsmentdiagnosztika és a szakértői analitika mint a hatékony vállalatirányítás eszközeinek fogalmi alapjait és módszertani megközelítéseit vizsgálja. A menedzsmentdiagnosztika a vállalkozás működésének szisztematikus kutatási és értékelési folyamata, amelynek célja a gazdasági, pénzügyi és szervezeti mutatók elemzése, amely a tényleges teljesítményeredmények, a belső és külső befolyásoló tényezők, valamint más releváns információk tanulmányozásán alapul a problémák azonosítása, a fejlesztési tartalékok meghatározása, a vezetői döntések hatékonyságának értékelése és a vállalkozás jövőbeli fejlődésére vonatkozó ajánlások megfogalmazása céljából. A szakértői analitika ehelyett a hosszú távú előrejelzésre, a belső és külső tényezők közötti kapcsolatok elemzésére, valamint a stratégiai döntések megalapozására összpontosít. A cikk rávilágít az e megközelítések közötti főbb különbségekre az olyan jellemzők tekintetében, mint a cél, a célkitűzések, a módszerek, a kutatás tárgya és tárgya, valamint alkalmazásuk eredményei A menedzsmentdiagnosztika a jelenlegi folyamatok elemzésére és a működési problémák hatékony megoldására irányul, míg a szakértői analitika a hosszú távú döntéshozatal információs alapját képezi, figyelembe véve a makrogazdasági és iparági változásokat. Különös figyelm van fordítva e megközelítések egymást kiegészítő jellegére a modern menedzsmentben, ami lehetővé teszi egy holisztikus elemzési rendszer létrehozását, amelynek célja a vállalkozás hatékonyságának fenntartása rövid és hosszú távon. Megállapítást nyer, hogy a menedzsmentdiagnosztika és a szakértői analitika integrációja lehetővé teszi a vezetők számára, hogy világos képet kapjanak a vállalkozás állapotáról, a potenciális veszélyekről és a fejlesztési lehetőségekről.

Резюме. У сучасних умовах підприємства змушені оперативно реагувати на численні зовнішні та внутрішні фактори, які впливають на їхню діяльність. Управлінська діагностика та експертна аналітика відіграють важливу роль у процесі управління, забезпечуючи керівників необхідною інформацією для прийняття обґрунтованих рішень і оцінки перспектив діяльності підприємства. Однак відсутність чіткого методологічного підґрунтя та розмежування цих підходів ускладнює їхнє ефективне використання в управлінні підприємством. У статті досліджено концептуальні основи та методологічні підходи до управлінської діагностики й експертної аналітики як інструментів ефективного управління підприємством. Управлінська діагностика визначена як системний процес дослідження та оцінки функціонування підприємства, спрямований на аналіз економічних, фінансових та організаційних показників, який ґрунтується на вивченні фактичних результатів діяльності, внутрішніх та зовнішніх факторів впливу, а також іншої релевантної інформації з метою ідентифікації проблем, визначення резервів для покращення, оцінки ефективності прийнятих управлінських рішень і формування рекомендацій щодо перспективного розвитку підприємства. Натомість експертна аналітика орієнтована на довгострокове прогнозування, аналіз взаємозв’язків між внутрішніми та зовнішніми чинниками і формування основ для стратегічних рішень. Висвітлено основні відмінності між цими підходами за такими характеристиками, як мета, завдання, методи, предмет і об’єкт дослідження, а також результати їхнього застосування. Управлінська діагностика спрямована на аналіз поточних процесів і ефективне вирішення оперативних проблем, тоді як експертна аналітика формує інформаційну основу для прийняття довгострокових рішень, враховуючи макроекономічні та галузеві зміни. Особливу увагу приділено взаємодоповнюваності цих підходів у сучасному управлінні, що дозволяє створити цілісну систему аналізу, спрямовану на підтримання ефективності підприємства в коротко- та довгостроковій перспективі. Встановлено, що інтеграція управлінської діагностики та експертної аналітики дає змогу керівникам отримати чітке уявлення про стан підприємства, потенційні загрози та можливості для розвитку.
Методологічні підходи до управлінської діагностики і експертної аналітики в управлінні підприємством
A vezetési diagnosztika és a szakértői elemzés módszertani megközelítései a vállalatirányításban
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/8
Keywords: management diagnostics; expert analytics; analysis; diagnostic methods; economic research; management decisions